Dialysis vintage stratified comparison of body composition, hydration and nutritional state in peritoneal dialysis and hemodialysis patients - Hoppe, Krzysztof (Arch Med Sci, 2016)
INTRODUCTION: Body mass decomposition and hydration state imbalances affect patients on maintenance dialysis. We compared body composition, hydration and nutritional state of patients on peritoneal dialysis (PD) and hemodialysis (HD) based on dialysis vintage (DV). MATERIAL AND METHODS: Three hundred and fifty-nine prevalent patients on HD (n = 301) and PD (n = 58) were divided into 3 subgroups depending on DV: < 2 years HD (n = 41) and PD (n = 28), 2–4 years HD (n = 111) and PD (n = 17), > 4 years HD (n = 149) and PD (n = 13). Bioimpedance analysis delivered data including overhydration (OH), Lean (LTM) and adipose lipids mass (FAT). Other measurements included daily diuresis (DD), subjective global assessment (SGA) and serum albumin (alb), C-reactive protein (CRP) and total cholesterol (TChol), and hemoglobin (Hb). RESULTS: Dialysis vintage < 2 years. Hemodialysis patients were older (65.5 ±18.5 vs. 50.9 ±17.1; p < 0.01) with a higher mortality (28 vs. 1; p < 0.01) and OH (8.0 ±4.3 vs. 1.6 ±3.1; p < 0.001). Hemoglobin (10.6 ±1.5 vs. 11.8 ±1.7; p < 0.05), TChol (180.2 ±47.0 vs. 211.7 ±46.3; p < 0.05), DD (871 ±729 vs. 1695 ±960; p < 0.001) and LTM (46.5 ±12.9 vs. 53.8 ±14.4; p < 0.05) were lower on HD. Dialysis vintage 2–4 years: when compared to PD, HD patients had higher OH (11.7 ±5.9 vs. 2.1 ±3.2; p < 0.001) and lower Hb (10.8 ±1.5 vs. 11.9 ±1.4; p < 0.01). Dialysis vintage > 4 years: compared to PD, HD patients had higher LTM (44.3 ±11.7 vs. 38.6 ±7.9; p < 0.05) and lower FAT (34.4 ±11.1 vs. 42.8 ±6.4; p < 0.01). CONCLUSIONS: Dialysis patients’ body composition depends on dialysis modality and DV. Dialysis vintage < 2 years is associated with better hydration, nutritional state, and survival in PD patients, but longer DV reduces these benefits. Dialysis vintage > 4 years associated with similar hydration and mortality in both PD and HD while body composition was better on HD.